Untangling the Overexploitation Trap: Governance, Politics of Concepts, and the Sustainability Claims of Chilean Southern Hake - Manuel E. Martínez‐González; Renato Gozzer‐Wuest; Enrique Alonso‐Población; Juan Alfaro‐Fuentes; José T. Montero; Rodrigo Wiff (Fisheries Management and Ecology, 2026)
Despite a 2013 legal reform introducing polycentric governance and an active Marine Stewardship Council (MSC) certification, persistent overexploitation of Chilean Southern hake ( Merluccius australis ) raises fundamental questions about how institutional arrangements embedding participatory management and science‐based decision‐making actually shape management outcomes. We systematically analyzed all 54 meeting minutes of Chile's Scientific Technical Committee for Demersal Resources in the Southern Austral Zone (STC‐DRSAZ) spanning its full operational period (December 2013—October 2025), covering 15 quota recommendations and 49 sessions addressing Southern hake. We reconstructed governance dynamics through a four‐category typology of decision‐making majorities and a thematic analysis of technical opinions during STC‐DRSAZ sessions. Stock status shows a slight but insufficient recovery trend (slope = 0.006/year, p ~0.02), with spawning biomass stabilized around SB t /SB 0 ~0.3—well below the MSY target of 0.4. The records reveal that management authorities exceeded STC quota recommendations in 2018 (+24%) and 2019 (+31%), and that in 20 of 36 meeting minutes, STC members expressed critical opinions on the effectiveness of the Decision Control Rules (DCRs)—distilled into seven recurring premises—ultimately leading the STC to informally abandon their application in 2024–2026. We conceptualize these dynamics as an overexploitation trap sustained by rather static DCRs that function as a political artifact rather than a science‐based management tool, entrench a short‐term management perspective, and structurally constrain the effectiveness of independent scientific advice. This trap is not a single‐stock phenomenon: the absence of legally mandated recovery programs affects six other major Patagonian demersal fisheries. Finally, we find no evidence that MSC certification has prompted meaningful improvements in stock status, lending support to growing concerns that premature market recognition may discourage rather than incentivize genuine sustainability gains.